2022
DOI: 10.1371/journal.ppat.1009977
|View full text |Cite|
|
Sign up to set email alerts
|

A revised mechanism for how Plasmodium falciparum recruits and exports proteins into its erythrocytic host cell

Abstract: Plasmodium falciparum exports ~10% of its proteome into its host erythrocyte to modify the host cell’s physiology. The Plasmodium export element (PEXEL) motif contained within the N-terminus of most exported proteins directs the trafficking of those proteins into the erythrocyte. To reach the host cell, the PEXEL motif of exported proteins is processed by the endoplasmic reticulum (ER) resident aspartyl protease plasmepsin V. Then, following secretion into the parasite-encasing parasitophorous vacuole, the mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(80 citation statements)
references
References 71 publications
6
74
0
Order By: Relevance
“…However, there is some evidence emerging that suggests that PfHsp70-2 and PfHsp70-x (and potentially other chaperones/co-chaperones such as PfJDPs) may collaborate with the core threading machinery of PTEX, a class I AAA + ATPase (PfHsp101; Russo et al, 2010 ; Matthews et al, 2019 ) in the chaperoning of exported P. falciparum proteins. For example, it has been shown that PfHsp101 is localized to the ER and the PV ( Russo et al, 2010 ), and is able to preferentially associate with certain PEXEL-containing proteins within these compartments ( Gabriela et al, 2022 ). PfHsp70-2 has been shown to not only interact with proteins secreted into the PV, but also with exported proteins, including the main virulence factor P. falciparum erythrocyte membrane protein 1 (PfEMP1; Saridaki et al, 2008 ; Batinovic et al, 2017 ; Cortés et al, 2020 ).…”
Section: Pfhsp70s Are the Guardians Of The Parasite-resident And Expo...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is some evidence emerging that suggests that PfHsp70-2 and PfHsp70-x (and potentially other chaperones/co-chaperones such as PfJDPs) may collaborate with the core threading machinery of PTEX, a class I AAA + ATPase (PfHsp101; Russo et al, 2010 ; Matthews et al, 2019 ) in the chaperoning of exported P. falciparum proteins. For example, it has been shown that PfHsp101 is localized to the ER and the PV ( Russo et al, 2010 ), and is able to preferentially associate with certain PEXEL-containing proteins within these compartments ( Gabriela et al, 2022 ). PfHsp70-2 has been shown to not only interact with proteins secreted into the PV, but also with exported proteins, including the main virulence factor P. falciparum erythrocyte membrane protein 1 (PfEMP1; Saridaki et al, 2008 ; Batinovic et al, 2017 ; Cortés et al, 2020 ).…”
Section: Pfhsp70s Are the Guardians Of The Parasite-resident And Expo...mentioning
confidence: 99%
“…As mentioned in the previous section, two of the exported PfJDPs (PFA0660w and PFE0055c) associate with PfHsp70-x in J-dots within the erythrocyte cytosol ( Külzer et al, 2010 ; Külzer et al, 2012 ; Grover et al, 2013 ; Petersen et al, 2016 ), and have been shown to be co-chaperones of PfHsp70-x ( Daniyan et al, 2016 ; Dutta et al, 2021b ). It has been proposed that these J-dots play a role in the trafficking and folding of exported proteins ( Külzer et al, 2012 ; Behl et al, 2019 ; Gabriela et al, 2022 ). Interestingly, one of the J-Dot PfJDPs, PFE0055c, was found to be essential ( Zhang et al, 2018 ), while the other (PFA0660w) was not.…”
Section: Pfjdps Harness the Chaperone Power Of Parasite And Host Hsp70smentioning
confidence: 99%
See 1 more Smart Citation
“…As MMV396797 appeared by microscopy to block protein export within the parasite, it seems unlikely that this compound targets PTEX150 or EXP2, which reside at the PVM. While HSP101 is dually located at the PVM and the parasite ER 46 , the relative lack of PEXEL protein blocked in the PV space after MMV396797 treatment suggests that it is unlikely to also be the target of this compound.…”
Section: An Essential Component Of the Protein Export Pathway Is Ptex...mentioning
confidence: 99%
“…The importance of protein export for parasite survival is demonstrated by knocking-down expression of PTEX proteins which results in rapid parasite death 37,39 . HSP101 appears to first recognise protein cargos in the ER and accompany them to PTEX for translocation into the RBC indicating HSP101 inhibitors might result in protein cargoes becoming trapped in the ER and parasitophorous vacuole (PV) 45,46 .…”
Section: Introductionmentioning
confidence: 99%